Improving Performance of Nursing Documentation Based on Knowledge Management Through Seci Concept Model’s - R. Arief Santoso; Widodo J. Pudjirahardjo (Universitas Airlangga, 2013)
Introduction: Documentation of nursing care in Kalianget RSI in 2011 was totaled average 58,1% and in 2012 achieve was still low. According the lowest component was nursing diagnosis. This research aims to improve the performance of nursing care documentation based on knowledge management through the SECI Model’s concept in Garam Kalianget RSI Sumenep District.Method: Design of this research was action research. Population and sample in the research of knowledge, motivation and work responsibility were all nurses total ed 29 people. The dependent variable were knowledge, performance, motivation, work responsibility, and performance after intervention knowledge management (KM) and as independent variable in this research was knowledge, performance, and intervention research knowledge management in documentation nursing care. Data were collected by using questionnaires and checklists.Result: The results after the SECI model’s intervention and using Paired t Test with a 95% confidence level of knowledge obtained p = 0.0001 which means that there was a significant knowledge difference between before and after intervention, comparison of performance documenting of nursing care obtained value ρ = 0.004, which means there was a difference significant performance between before and after intervention. Comparison of SBAR effective communication performance values obtained ρ = 0.001, which means there was a significant performance difference between before and after intervention.Discussion: Knowledge management through SECI model’s has important role in improving performance documentation of nursing care and SBAR effective communication. It is recommended to do in forum sharing nurse’s experience or informant in practical communication in periodic, recording, documentation, and keep document well and doing supervision continously especially form nursing care and SBAR effective communication.